General equilibrium analysis on simulation of macroeconomic policy changes and it's effects on the economic relationship between Singapore and Malaysia. - Koh, Pee Teck. (2008)
This research paper attempts to present a theoretical analysis of several macroeconomic policy changes based on an aggregated 8 sectors of the Singapore and Malaysia economies. Changes of macroeconomic policies, more specificially , wages, exchange rate and interest rate policies of both countries will be made to analyse the trade relationship between Singapore and Malaysia.